Reflection Habituation on The Online Tutorial - Mestika Sekarwinahyu; Amalia Sapriati; Ucu Rahayu (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2022)
This study aims to produce a reflective learning program that can be applied to the online tutorial for the final project to improve students' reflective thinking skills. Through a series of phased activities, a reflective learning program using discussion as the core of activities followed by reflection activities using the Gibbs’ reflective cycle has produced a reflective learning program in an online tutorial that is ready to be tested. The test was conducted to measure the students' reflective thinking level before and after using the program using the Kember reflective thinking level instrument. The study show that the program has the main characteristic of sharpening students' reflective thinking skills.  After using the program, students' reflective thinking skills showed an increase in the highest score at the critical reflection level. The program has the advantage that students will get used to doing reflection and can practice higher-order thinking skills through discussion activities. Program limitations occurred because of the effect of program characteristics, namely, students must have high motivation, discipline, and independent learning, students must have sufficient computer and IT skill.  The program has the potential to increase the ability of reflection to support a change/shift towards a higher level of reflective thinking.